Ruling destiny - Noel, Alyson; Noel, Alyson (Shrewsbury, PA Entangled Teen, an imprint of Entangled Publishing LLC, 2023)
"Forced to pair up with Killian on a new assignment in Renaissance Italy, Natasha soon discovers his task is nothing like hers and learns the startling truth behind Arthur's ultimate invention that would allow him to control time--and control the world"--
111774
Keywords: Fate and fatalism -- Juvenile fiction; Time travel -- Juvenile fiction; Private schools -- Juvenile fiction; High school students -- Juvenile fiction; Boarding schools -- Fiction; Fantasy fiction; Time-travel fiction; School fiction; Novels